Microbial and molecular signatures for enhanced gut health in pigs fed a diet with spray-dried plasma as functional protein source - Kar, Soumya K.; Schokker, Dirkjan; van Vuure, Carine; van Iersel, Herman; Harms, Amy C.; Kruijt, Leo; Smits, Mari A.; Jansman, Alfons J. M. (Frontiers in Animal Science, 2025)
This study investigates the effects of dietary spray-dried plasma (SDP) supplementation on the gut and health of growing pigs using an advanced “FeedOmics” approach. This integrative methodology employs a range of omics-based techniques to analyze microbial and molecular “signatures” associated with the dietary impact of SDP. Sixteen male growing pigs (34.9 ± 3.4 kg, 10–11 week old; n = 8/treatment group) were randomly assigned to receive one of two experimental diets for three weeks. These diets were prepared with one of the following protein sources containing (as fed basis): soybean meal (SBM, 343 g/kg), or SDP protein (SDPP, 196 g/kg). At the end of the trial, pigs were euthanized to collect jejunal and ileal mucosal tissues for gene expression analysis, jejunal and ileal digesta for microbiota profiling, blood plasma for systemic metabolomic assessment, and serum for cytokine and chemokine quantification. The SBM-based diet group was used as the reference. Findings indicate that SDPP influences the jejunum more than the ileum, where it causes a significant reduction in bacterial alpha diversity (P < 0.05) compared to SBM. We report a significant (P < 0.05) decrease in the relative abundance of the Sarcina genera in the small intestine, an effect comparable to pharmaceutical concentrations of zinc oxide (ZnO). Transcriptomic analysis identified 319 genes with altered expression in the jejunal mucosal tissue. Notably, SDPP upregulated tight junction receptors in the jejunum, which suggests it improves intestinal integrity by strengthening the gut barrier. We measured metabolites like threonine, taurine, and glutamine/glutamate in the blood of SDPP-fed pigs. These metabolites act as distinctive “fingerprints,” contributing to gut health by providing cellular energy, restoring tight junctions, and orchestrating immune responses in the small intestine mucosa. Overall, our results highlight the nutritional and functional value of SDP as functional dietary protein source.